Nurses' and patients' perceptions of physical health screening for patients with schizophrenia spectrum disorders : a qualitative study - Långstedt, Camilla (BioMed Central, 2025)
Background: Despite worldwide concern about the poor physical health of patients with schizophrenia spectrum disorders (SSD), physical health screening rates are low. This study reports nurses' and patients' experiences of physical health screening among people with SSD using the Finnish Health Improvement Profile (HIP-F) and their ideas for implementation improvements.
Methods: A qualitative exploratory study design with five group interviews with nurses (n = 15) and individual interviews with patients with SSD (n = 8) who had experience using the HIP-F in psychiatric outpatient clinics. Inductive content analysis was conducted.
Results: Two main categories were identified. First, the characteristics of the HIP-F were divided into the subcategories of comprehensive nature, facilitating engagement, interpretation and rating of some items and duration of screening. Second, suggestions for the implementation of physical health screening consisted of two subcategories: improvements in screening and ideas for practice. Physical health screening was felt to increase the discussion and awareness of physical health and supported health promotion. The HIP-F was found to be a structured, comprehensive screening tool that included several items that were not otherwise assessed in clinical practice. The HIP-F was also considered to facilitate engagement by promoting collaboration in an interactive way. Despite this, most of the nurses found the HIP-F to be arduous and too time consuming, while patients found the HIP-F easy to use. Nurses found some items unclear and infeasible, while patients found all items feasible. Based on the nurses' experiences, screening should be clear and easy to interpret, and condensation and revision of the HIP-F tool were suggested. The patients did not think that any improvements to the HIP-F were needed for implementation in clinical settings.
Conclusions: Patients with schizophrenia spectrum disorders are willing to participate in physical health screening. Physical health screening should be clear, easy to use and relatively quick. With this detailed knowledge of perceptions of screening, further research is needed to understand what factors affect the fidelity of implementing physical health screening in clinical mental health practice and to gain an overall understanding on how to improve such implementation.